Brightness variations of young Sun-like stars from ground-based and space telescopes. Issue Volume 14:Issue S345(2019) (August 2018) - Zsidi, G.; Kóspál, Á.; Ábrahám, P.; Szabó, R.; Cseh, B.; Sárneczky, K.; Sódor, Á.; Szakáts, R.; Vida, K.; Vinkó, J.
Abstract: Young stellar objects often show photometric variability, which is well examined at optical wavelengths, but more and more infrared data are also available. The wavelength dependence of the variability carries information on the physical cause of the changing brightness. Here, we examine seven T Tauri-type stars known for their large amplitude variability selected from the Campaign 13 field of the Kepler K2 mission. We complemented the K2 light curves by multifilter optical monitoring observations made with the 90 cm Schmidt telescope of Konkoly Observatory, and by 3.6 and 4.5 μ m infrared photometry with a 20 hours cadence using the Spitzer Space Telescope. We found that the wavelength dependence of the observed variability is not consistent with changing interstellar extinction. We suggest that the brightness changes are due to variable accretion, causing a variable illumination of the inner disk.